2003
DOI: 10.1007/s00299-003-0676-8
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration and Agrobacterium- mediated transformation of hop ( Humulus lupulus L.)

Abstract: An efficient procedure for direct organogenesis and regeneration of hop (Humulus lupulus L.) was established. For the first time Agrobacterium-mediated genetic transformation of hop (cv. "Tettnanger") was achieved. Shoot internodes from in vitro cultures were identified as the most suitable type of explant for regeneration. Using this type of explant, a shoot-inducing medium was developed that supported direct organogenesis of approximately 50% of the explants. Plantlets were successfully rooted and transferre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 18 publications
0
27
0
2
Order By: Relevance
“…Monocotyledonous plants, in particular cereal plants, are naturally outside of the host range of A. tumefaciens, however, so the development of a system for the genetic transformation of monocotyledons has been slow (Hiei et al 1997). Nonetheless, successful transformations has been reported in some monocotyledonous plants, including Oryza (Hiei et al 1994), Hordeum (Tingay et al 1997), Humulus (Horlemann et al 2003) and Alstroemeria (Akutsu et al 2004). The bombardment of cells and tissues, another option for genetic improvement, has been attempted in many plant species (Iida et al 1991;Christou et al 1992;Batista et al 2008).…”
Section: Introductionmentioning
confidence: 94%
“…Monocotyledonous plants, in particular cereal plants, are naturally outside of the host range of A. tumefaciens, however, so the development of a system for the genetic transformation of monocotyledons has been slow (Hiei et al 1997). Nonetheless, successful transformations has been reported in some monocotyledonous plants, including Oryza (Hiei et al 1994), Hordeum (Tingay et al 1997), Humulus (Horlemann et al 2003) and Alstroemeria (Akutsu et al 2004). The bombardment of cells and tissues, another option for genetic improvement, has been attempted in many plant species (Iida et al 1991;Christou et al 1992;Batista et al 2008).…”
Section: Introductionmentioning
confidence: 94%
“…Škof and Luthar ( 2005 ) reported the Agrobacteriummediated genetic transformation of H. Lupulus introducing gus reporter gene. Many other authors have also reported the effi cient transformation and regeneration system of H. lupulus (Horlemann et al 2003 ;Schwekendiek et al 2005 ;Batista et al 2008 ). Bombarded with the plasmid pSR5-2 ( gusA and nptII ), delivery into H. lupulus organogenic calli using the gene gun system was also reported by .…”
Section: Humulus Lupulus Lmentioning
confidence: 86%
“…Tento první názorný pří-klad transgenního metabolomu u chmelu by měl být v budoucnu ná-sledován cílenějšími změnami podle toho, jak bude postupovat analýza genetické determinace biochemických drah účastnících se v syntéze chmelového metabolomu. Transgenní pletiva chmelu lze v současnosti získat klasickým způsobem při použití transformace bakteriemi A. tumefaciens (Oriniaková et al, 1996) a regenerace na selekčním médiu (Horlemann et al, 2003, Schwekendiek et al, 2007 nebo s použitím biolistické metody (Batista et al, 2008), i když v obou případech je oproti některým jiným rostlinným druhům efektivita transformace stále nízká (Horlemann et al, 2003). V obou přípa-dech lze úspěšně využít klasické monocistronické transformační vektory, tj.…”
Section: Transgenní Chmel a Způsoby Jeho Přípravy Pro Získání Modifikunclassified
“…This first illustrative example of transgenic metabolome in hop should be followed up with the targeted application of transgenosis in connection to the progress of our knowledge of biosynthesis pathways of hop metabolome. At present the transgenic hop tissues can be prepared either by a classical way using A. tumefaciens-mediated (Oriniaková et al, 1996) transformation and regeneration on selection media (Horlemann et al, 2003, Schwekendiek et al, 2007 or with the use of biolistic method (Batista et al, 2008), although in both cases the efficiency of hop transformation is still low in comparison with some other plant species (Horlemann et al, 2003). In both transformation methods it is possible to use classical monocistronic plant binary vectors i.e.…”
Section: Transgenic Hop and The Ways Of Its Preparation To Gain Modifmentioning
confidence: 99%